Tandem Mass Tag labelling quantitative acetylome analysis of differentially modified proteins during mycoparasitism of Clonostachys chloroleuca 67–1 - Na Jiang (Nature Portfolio, 2021)
Abstract Lysine acetylation (Kac) is an important post-translational modification (PTM) of proteins in all organisms, but its functions have not been extensively explored in filamentous fungi. In this study, a Tandem Mass Tag (TMT) labelling lysine acetylome was constructed, and differentially modified Kac proteins were quantified during mycoparasitism and vegetative growth in the biocontrol fungus Clonostachys chloroleuca 67–1, using liquid chromatography-tandem mass spectrometry (LC–MS/MS). A total of 1448 Kac sites were detected on 740 Kac proteins, among which 126 sites on 103 proteins were differentially regulated. Systematic bioinformatics analyses indicate that the modified Kac proteins were from multiple subcellular localizations and involved in diverse functions including chromatin assembly, glycometabolism and redox activities. All Kac sites were characterized by 10 motifs, including the novel CxxKac motif. The results suggest that Kac proteins may have effects of broadly regulating protein interaction networks during C. chloroleuca parasitism to Sclerotinia sclerotiorum sclerotia. This is the first report of a correlation between Kac events and the biocontrol activity of C. chloroleuca. Our findings provide insight into the molecular mechanisms underlying C. chloroleuca control of plant fungal pathogens regulated by Kac proteins.